Transferable scoring function based on semiempirical quantum mechanical PM6-DH2 method: CDK2 with 15 structurally diverse inhibitors - Dobeš, Petr; Fanfrlík, Jindřich; Řezáč, Jan; Otyepka, Michal; Hobza, Pavel (Journal of computer-aided molecular design, 2011)
A semiempirical quantum mechanical PM6-DH2 method accurately covering the dispersion interaction and H-bonding was used to score fifteen structurally diverse CDK2 inhibitors. The geometries of all the complexes were taken from the X-ray structures and were reoptimised by the PM6-DH2 method in continuum water. The total scoring function was constructed as an estimate of the binding free energy, i.e., as a sum of the interaction enthalpy, interaction entropy and the corrections for the inhibitor desolvation and deformation energies. The applied scoring function contains a clear thermodynamical terms and does not involve any adjustable empirical parameter. The best correlations with the experimental inhibition constants (ln K (i)) were found for bare interaction enthalpy (r (2) = 0.87) and interaction enthalpy corrected for ligand desolvation and deformation energies (r (2) = 0.77); when the entropic term was considered, however, the correlation becomes worse but still acceptable (r (2) = 0.52). The resulting correlation based on the PM6-DH2 scoring function is better than previously published function based on various docking/scoring, SAR studies or advanced QM/MM approach, however, the robustness is limited by number of available experimental data used in the correlation. Since a very similar correlation between the experimental and theoretical results was found also for a different system of the HIV-1 protease, the suggested scoring function based on the PM6-DH2 method seems to be applicable in drug design, even if diverse protein-ligand complexes have to be ranked.
Keywords: Protein Kinase Inhibitors; Protein Binding; molekulární modely; Cyclin-Dependent Kinase 2; Drug Design; racionální návrh léčiv; Ligands; termodynamika; vazba proteinů; Models, Molecular; Quantum Theory; cyklin-dependentní kinasa 2; kvantová teorie; lidé; ligandy; inhibitory proteinkinas; Humans; Thermodynamics